Motivation and Prevention of Difficulties in the Learning of Sciences: Applying Strategies of Emotional Intelligence, Neuroscience and Educational Coaching in the Primary Classroom - Zamorano Chico, Cristina (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2019)
The latest advances in neuroeducation have shown that emotions are the doorway to learning. In other words, in the teaching-learning process emotions are previous to and interwoven with cognitive processing. The degree of abstraction implied in the learning of Science and Maths frequently triggers negative emotions and thoughts that cause discouragement and frustration in students, that may eventually turn into unconscious beliefs about their own learning capacity in these subjects. This paper aims to explain how demotivation and learning difficulties in Science subjects occur due to emotional blunting and the rise of unconscious beliefs. A set of strategies based on emotional intelligence, neuroeducation and educational coaching is proposed in order to develop an effective teaching of Sciences and Maths in Primary Education, strategies that could also be applied to the teaching-learning process of any other discipline.